2012
DOI: 10.1002/chem.201202930
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Kinetics of Open‐Chain and Macrocyclic Gadolinium(III)‐Aminopolycarboxylate Complexes Related to Magnetic Resonance Imaging: Catalytic Effect of Endogenous Ligands

Abstract: The kinetics of the metal exchange reactions between open-chain Gd(DTPA)(2-) and Gd(DTPA-BMA), macrocyclic Gd(DOTA)(-) and Gd(HP-DO3A) complexes, and Cu(2+)  ions were investigated in the presence of endogenous citrate, phosphate, carbonate and histidinate ligands in the pH range 6-8 in NaCl (0.15 M) at 25 °C. The rates of the exchange reactions of Gd(DTPA)(2-) and Gd(DTPA-BMA) are independent of the Cu(2+) concentration in the presence of citrate and the reactions occur via the dissociation of Gd(3+)  complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 62 publications
(216 reference statements)
3
101
0
2
Order By: Relevance
“…The Gd 3+ chelates of DOTA and its derivatives are more thermodynamically stable and more kinetically robust than their DTPA counterparts. 22 They are more suitable for applications that require prolonged in vivo lifetimes, and controversy surrounds the isolated cases in which GdDOTA has been associated cases of NSF. 23 In general, DOTA derivatives are considered sufficiently stable for prolonged in vivo residence lifetimes, and therefore for targeted applications.…”
Section: Introductionmentioning
confidence: 99%
“…The Gd 3+ chelates of DOTA and its derivatives are more thermodynamically stable and more kinetically robust than their DTPA counterparts. 22 They are more suitable for applications that require prolonged in vivo lifetimes, and controversy surrounds the isolated cases in which GdDOTA has been associated cases of NSF. 23 In general, DOTA derivatives are considered sufficiently stable for prolonged in vivo residence lifetimes, and therefore for targeted applications.…”
Section: Introductionmentioning
confidence: 99%
“…partly contribute to this dissociation. (23) No transmetallation was detected in samples containing Gd-DOTA or Gd-DOTA-Am4 over the course of 72 hours. Therefore, it can be concluded that Gd-DOTA-Am4 is significantly more stable than Gd-DTPA.…”
Section: Resultsmentioning
confidence: 94%
“…Por ejemplo, gadodiamida tiene una vida media de 2 h en individuos sanos con función renal normal y aumenta a alrededor de 30 h en pacientes con ERC etapa 5 36 . El gadolinio libre puede unirse a aniones disponibles en el medio como fosfato, formando sales insolubles y depositándose en los tejidos 37 . Se ha detectado depósitos de gadolinio en biopsias de piel 38,39 y otros tejidos de pacientes con FSN 40,41 , pero no en la piel de individuos sanos expuestos a MC basados en gadolinio 42 .…”
Section: Fisiopatologíaunclassified